KARAKTERISTIK PASIEN DENGAN GANGGUAN FUNGSI HATI DI RSUD SULTAN SYARIF MOHAMAD ALKADRIE KOTA PONTIANAK TAHUN 2017 - ., Melfa Dewita Ines (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Liver damage caused by drugs is liver damage related to liver function disorderscaused by drugs exposure or other noninfectious agents. This study aims todetermine the profile of patients with impaired liver function. This method isobservational with the study design being descriptive cross sectional. The researchdata of each patient was analyzed using supporting literature. Data retrieval wasdone retrospectively through medical records of inpatients with liver functiondisorders at Sultan Syarif Mohamad Alkadrie Hospital in Pontianak in April-May2018. The research subjects who fulfilled the inclusion criteria were 33 people. Theresults showed that the profile of patients based on sex found that male patients hadmore liver disease compared to female patients, the profile of patients suffering fromliver disease based on the age at most at the age of 45-60 years, the profile ofpatients based on diagnoses found to be the most common disease patients liver ishepatitis B. Conclusion of this study is that patients who suffer the most from liverdisease are men aged 45-60 years, with the most diagnosed is hepatitis B.conductedby observational method with the descriptive cross sectional research design andthen the data wereKey words : profile of patients liver disease, liver disfunction